Potential for Sustainable Irrigation towards Food Self-Sufficiency in Sierra Leone - Juana P. Moiwo; Mohamed M. Blango; Yahaya K. Kawa; Alhaji M. H. Conteh (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
The world population has been growing since creation and what was not a concern has now become a harsh challenging issue of our time — food production, security and self-sufficiency. With land being available and weather conducive, the next most critical requirement for crop production is water. Although two-thirds of the earth’s surface is covered with water, some 70% of it is not readily usable, especially for crop production. Rainwater, surface water and groundwater are the three most common sources of water used in crop cultivation. While any of these can be scarce in most parts of the world, all the three sources of water are abundant in Sierra Leone. But availability is only one side of resource development. The other vey important side of resource development is efficiently harnessing an available resource to adequately serve an intended purpose. Over 40% of food production in the world today is done on the 17% arable land that is irrigated. This shows the potential for food production, food security and food self-sufficiency under irrigated agriculture. In spite of this compelling indicator, only 0.6% of the arable land (74% of the land area of Sierra Leone) is irrigated. The objective of this study was to assess the potential for food security and food self-sufficiency in Sierra Leone. Given the current land productivity, the study showed that only 31% of the available water resources was needed to irrigate only 19% of the arable land to attain food self-sufficiency in Sierra Leone. In fat, investment in water resources and arable land for nation-wide irrigation can ensure food crop production sufficient to support export. This can ease the pressure on the nation to build the needed forex to support import businesses.